Aute Life: Indigenous Living, Indigenous Dyeing - Te Punga Somerville, Alice (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2024)
How can, and do, Indigenous thinkers and artists reckon with the simultaneous horrors and vibrancy of the long eighteenth century? Aute is the NZ Māori name for a kind of cloth created from the paper mulberry plant across the Pacific region that is more widely known as tapa. Tracing the ends and new beginnings of aute production, paying attention to three different moments in which I have connected with eighteenth-century tapa, and reciting a multi-directional genealogy of Indigenous people who engage directly with tapa and/or the eighteenth century, I propose the concept of ‘Aute life.’ Ultimately, ‘Aute life’ is an orientation to the eighteenth century that centres Indigenous critical and creative engagements with that period; attending to dying and dyeing, it reframes absence or loss as presence or continuity, and pushes us to reconsider the limits and possibilities of who we think does work on, or with, the eighteenth century.